Shakarim’s «Religion of the Soul». Three faces of the «Beloved» (Eurasian Journal of Philology Science and Education, 2020)
The article is devoted to the philosophy and poetics of Sufism in Shakarim’s poetry. The study of theoriginality of the Kazakh poet’s interpretation of Sufism took on the character of the concept of «religionof the soul»/ Shakarim’s «religion of the soul» is explored as the history of man’s inner path to God. Thetheme of love ‒ the ascent of the human spirit to the absolute-is interpreted by the poet as a personalexperience of mystical insight. Typical for Sufism motives: spiritual purification and insight throughtouching the mystery, sorcery of the Beloved, touching the lock of the Beloved, intoxication with wine,the disappearance of one’s self, and death are shown in three poems of Shakarim as the triumph of theabsolute and the creation of the world. A common theme for Shakarim’s lyrics is revealed: «I and God».The author analyzes the symbolism of intoxication as a comprehension of the Truth, the function of theimages of the «lock of the beloved», the Nightingale, the «beggar», and the Paradise houris. The specificsof the interpretation of Sufism by Shakarim is shown as an ethical and moral program for improving aperson and spiritual comprehension of the truth. The concepts of the spiritual Kingdom and the spiritualheart and pure mind are also studied as the basis of the poet’s worldview, which caused the genre originality of his poetry, philosophical and didactic at the same time.